Analysis Of Beef Traders' Income In Market Baru Karawang - Anggita larasati; Dedi Mulyadi; Santi Pertiwi Hari Sandi (Pusat Riset dan Inovasi Nasional, 2025)
Traditional markets according to Permendagri No. 42 of 2007, is a location where sellers and buyers meet to make transactions and become a means of social and cultural interaction of the community, as well as encouraging local economic growth. The purpose of this study was to analyze, calculate, and explain how the income of beef traders and what obstacles are faced by beef traders in the new market of Karawang. This study uses a quantitative descriptive approach. The location of the study was selected using the purposive sampling method, namely based on certain criteria that are considered relevant to the purpose of the study. The results of the study showed that the income and costs incurred by beef traders vary according to sales volume. The average income of beef traders per day is Rp. 8,305,083. The obstacles faced by beef entrepreneurs include the discounts and delivery services.